2016
DOI: 10.18632/oncotarget.11050
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mutation profile and prognostic relevance in patients with hypoplastic myelodysplastic syndromes (h-MDS)

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of hematologic malignancies. Although most MDS patients have normal or increased BM cellularity (NH-MDS), some have hypocellular BM (h-MDS). The reports concerning the differences in genetic alterations between h-MDS and NH-MDS patients are limited. In this study, 369 MDS patients diagnosed according to the WHO 2008 criteria were recruited. h-MDS patients had lower PB white blood cell and blast counts, and lower BM blast percentages, than those with NH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Targeted capture assays were carried out, on bone marrow DNA specimens, for the following genes: TET2 , DNMT3A , IDH1 , IDH2 , ASXL1 , EZH2 , SUZ12 , SRSF2 , SF3B1 , ZRSR2 , U2AF1 , PTPN11 , TP53 , SH2B3 , RUNX1 , CBL , NRAS , JAK2 , CSF3R , FLT3 , KIT , CALR , MPL , NPM1 , CEBPA , IKZF1 and SETBP1. Further details on mutation screening have been previously published and detailed in the supplement . A retrospective chart review was conducted in 357 consecutive patients with primary MDS.…”
Section: Methodssupporting
confidence: 87%
“…Targeted capture assays were carried out, on bone marrow DNA specimens, for the following genes: TET2 , DNMT3A , IDH1 , IDH2 , ASXL1 , EZH2 , SUZ12 , SRSF2 , SF3B1 , ZRSR2 , U2AF1 , PTPN11 , TP53 , SH2B3 , RUNX1 , CBL , NRAS , JAK2 , CSF3R , FLT3 , KIT , CALR , MPL , NPM1 , CEBPA , IKZF1 and SETBP1. Further details on mutation screening have been previously published and detailed in the supplement . A retrospective chart review was conducted in 357 consecutive patients with primary MDS.…”
Section: Methodssupporting
confidence: 87%
“… 22 , 23 In a recent study of 100 hypoplastic MDS patients, it was observed that these patients have statistically significant lower peripheral blood counts, bone marrow blast percentages and a lower incidence of poor-risk cytogenetic abnormalities, as compared to the non hypoplastic groups. 24 On the contrary, in our cohort of 9.3% (14/150) patients with hypoplastic MDS, the median blast count was 5% and 78% (7/9) of these patients were found to harbor abnormal karyotype ( Supplementary table 2 ).…”
Section: Discussionmentioning
confidence: 54%
“…Table 2 recapitulates the main cytogenetic and molecular aspects of normo/hypercellular MDS, hMDS, and AA. Since cytogenetic studies [ 6 , 12 , 15 , 16 ] showed no remarkable differences between non-hMDS and hMDS, although the latter more frequently show lower-risk karyotypes, the resolution achieved by molecular approaches may be particularly valuable. High-throughput next-generation sequencing (NGS) characterization represents a powerful tool to detect eventually ontogenetic and prognostic features distinctive of hMDS.…”
Section: Pathogenesismentioning
confidence: 99%
“…An initial study from Huang et al compared 37 hMDS patients to 152 non-hMDS patients of a single-center Taiwanese cohort, without scoring any significant difference in the prevalence of RAS, AML1, JAK2, PTPN11, and FLT3/ITD mutations [ 12 ]. More recently, two single-center studies [ 15 , 16 ] investigated selected gene mutations of known importance in myeloid disorders, comparing their prevalence in hMDS vs. non-hMDS patients. Nahza et al showed that hMDS was associated with fewer somatic mutations and smaller driver clones compared to non-hMDS (including both normo- and hypercellular MDS).…”
Section: Pathogenesismentioning
confidence: 99%